Measuring tools to help professional teachers: Valid and reliable perfectionist academic scale tools for students - Yulianingrum, Vivi; Athar, Samia (Universitas Ahmad Dahlan, 2024)
Every student hopes to succeed academically, but some students tend towards academic perfectionism, which can impact conditions at school. Professional teachers need to detect these characteristics, but there are no specific measuring instruments for elementary and secondary school students. Therefore, this study aims to develop and test the validity and reliability of the academic perfectionist scale. This scale was developed based on five main aspects: not taking assignments as a burden, being disciplined and consistent, having high grades, being afraid of failure, and having negative views of others. The research method used is a mixed sequential exploration, which combines qualitative and quantitative approaches in stages. Scale arranged from a literature review validated by experts and then analyzed qualitatively. Then, there is an empirical test using confirmatory factor analysis (CFA) with 108 respondents from Indonesia and Pakistan. The Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO MSA) results of 0.736 indicate that the data is sufficient for factor analysis. Of the 28 initial items, 24 have adequate validity with a loading factor value of ≥ 0.55. The reliability test with Cronbach’s Alpha produced a value of 0.718, indicating good internal consistency. This academic perfectionist scale is valid and reliable as a measuring tool for students’ academic perfectionism tendencies, which apply to educational and counselling interventions. The novelty is that this measuring tool applies at the elementary school level, from grade 3 to high school students (teenagers). However, further research is needed to test the external validity of this scale on a broader population.